2017
DOI: 10.1136/bmjopen-2016-015354
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of acne in Mainland China: a systematic review and meta-analysis

Abstract: IntroductionAcne, a very common skin disease, can result in psychological distress and sustain impairment in quality of life. Data on the prevalence of acne and the differences in gender, region and age are limited. The aim of this review is to estimate the prevalence of acne in Mainland China comprehensively and to quantify its association with gender, region and age.MethodsWe searched electronic databases with predetermined search terms to identify relevant studies published between 1 January 1996 and 30 Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
1
17
0
4
Order By: Relevance
“…9 Meanwhile, a meta-analysis in mainland China found a higher prevalence rate of acne in males than females, due to differences in lifestyle, skincare routines, and androgen levels. 6 In some other studies, no significant gender difference was noted and men and women are about equally affected. 10,11 We found high cholesterol levels in acne patients (P=0.025), particularly in men (P=0.04).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…9 Meanwhile, a meta-analysis in mainland China found a higher prevalence rate of acne in males than females, due to differences in lifestyle, skincare routines, and androgen levels. 6 In some other studies, no significant gender difference was noted and men and women are about equally affected. 10,11 We found high cholesterol levels in acne patients (P=0.025), particularly in men (P=0.04).…”
Section: Discussionmentioning
confidence: 85%
“…For instance, in a study the overall pooled prevalence rates of acne were 39.2%, the prevalence rates in different age groups were 10.2% overall, 50.2% for primary and secondary students and 44.5% for undergraduates. 6 Acne is no longer considered a health problem strictly of adolescence, as its prevalence in adults has significantly increased. 7 Overall, acne is more common in women, 8,9 but in some literature the prevalence is approximately equal in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Increased sebum excretion might cause acne to worsening. According to a systematic review and meta-analysis, the prevalence rates of acne in the southern China was higher than that of the northern China, because the southern part is more humid and warmer than the north ( 84 ). A study also showed that the higher the altitude, the lower the prevalence of acne, which may be related to higher altitudes and lower temperature and humidity ( 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nearly 80% of Americans will suffer from acne at some point in life time (Liu et al, 2015), and more than 50 million are facing this issue in the USA (White, 1998). In China, acne population prevalence is around 40%, and the rate rises to 50% in adolescents (Li et al, 2017). According to the study of the Global Burden of Disease, the acne population worldwide is 650 million, which made it one of the top 10 globally most prevalent diseases in 2010 (Hay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%